2008
DOI: 10.1111/j.1445-5994.2007.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of spontaneous intracerebral haemorrhage in haemodialysis patients and predictors of 30‐day mortality

Abstract: The outcome score is a simple clinical grading scale that allows risk stratification of HD patients presenting with ICH. This scale could be used to design treatment protocols and clinical research studies of ICH in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…This study therefore concluded that hyperglycaemia is probably a stress response to neurological injury. Moreover, a retrospective study in Taiwan [23] failed to reveal an independent relationship with 30-day mortality rates. The results in the present study show that admission hyperglycaemia is independently associated with early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This study therefore concluded that hyperglycaemia is probably a stress response to neurological injury. Moreover, a retrospective study in Taiwan [23] failed to reveal an independent relationship with 30-day mortality rates. The results in the present study show that admission hyperglycaemia is independently associated with early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although ICH incidence and long-term outcomes in maintenance HD patients have been well described, there have been few reports on the detailed clinical features of maintenance HD patients who experience ICH. Although previous studies show that the mortality rate in HD patients with acute ICH is high [14,15,16], no evidence has yet indicated that HD is an independent factor associated with early death on multivariate analysis. Moreover, some results of studies varied widely.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, the ROC curve displayed the threshold value of perihematma CBV was 1.24 ml·100 g −1 , and that of CBF Our study had the following limitations. The sample tcome in acute SICH are hematoma volume, Glasgow Coma Scale score, age, mass effect, and the presence of hydrocephalus [12,13]. We did not collect Glasgow Coma Scale data, and due to the small sample size, binary logical analysis was not applied for the risk factors for outcome.…”
Section: Discussionmentioning
confidence: 99%